A copy number variation genotyping method for aneuploidy detection in spontaneous abortion specimens. (19th January 2017) - Chen, Songchang; Liu, Deyuan; Zhang, Junyu; Li, Shuyuan; Zhang, Lanlan; Fan, Jianxia; Luo, Yuqin; Qian, Yeqing; Huang, Hefeng; Liu, Chao; Zhu, Huanhuan; Jiang, Zhengwen; et al.
Abstract: Objective: Chromosomal abnormalities such as aneuploidy have been shown to be responsible for causing spontaneous abortion. Genetic evaluation of abortions is currently underperformed. Screening for aneuploidy in the products of conception can help determine the etiology. We designed a high‐throughput ligation‐dependent probe amplification (HLPA) assay to examine aneuploidy of 24 chromosomes in miscarriage tissues and aimed to validate the performance of this technique. Methods: We carried out aneuploidy screening in 98 fetal tissue samples collected from female subjects with singleton pregnancies who experienced spontaneous abortion. The mean maternal age was 31.6 years (range: 24–43), and the mean gestational age was 10.2 weeks (range: 4.6–14.1). HLPA was performed in parallel with array comparative genomic hybridization, which is the gold standard for aneuploidy detection in clinical practices. The results from the two platforms were compared. Results: Forty‐nine out of ninety‐eight samples were found to be aneuploid. HLPA showed concordance with array comparative genomic hybridization in diagnosing aneuploidy. Conclusion: High‐throughput ligation‐dependent probe amplification is a rapid and accurate method for aneuploidy detection. It can be used as a cost‐effective screening procedure in clinical spontaneous abortions. © 2016 John Wiley & Sons, Ltd. Abstract : WHAT'S ALREADY KNOWN ABOUT THIS TOPIC? Chromosomal aneuploidy is a major factor that leads to spontaneous abortions. While most fetal aneuploidies are due to random meiotic errors, balanced chromosomal translocations of the parent(s) can cause recurrent miscarriages. Genetic evaluation of spontaneous abortions is currently underperformed. Several techniques are available for aneuploidy detection. However, the associated cost of these tests has prevented them from being performed on all patients who experienced miscarriages. WHAT DOES THIS STUDY ADD? This study establishes a simple PCR‐based approach to screen aneuploidy of 24 chromosomes in abortuses, which helps elucidate the etiology of miscarriages. If partial trisomy is detected in the products of conception, it is important to check for chromosomal translocations in both parents. The accuracy of this approach in detecting aneuploidy is comparable with array comparative genomic hybridization.